Evidentiary Ambivalence of Forensic Medical Reports: Analyzing Acquittal Judgments in Assault Cases - Zaldilah Mohamad Djali; Suwitno Yutye Imran; Ahmad (CV. Era Digital Nusantara, 2026)
The acquittal verdict in case Number 454/Pid.B/2024/PN.SBY concerning persecution resulting in death raises fundamental issues regarding the position of the Visum et Repertum (VeR) as valid evidence. This study aims to analyze the reasons behind the VeR being disregarded in the verdict and to examine its juridical and sociological consequences. Using normative juridical methods with statutory and case approaches, this research finds that the judge ignored the VeR without adequate legal reasoning, basing the decision solely on the lack of conviction regarding intent, despite the VeR meeting formal and material requirements and scientifically proving the causal relationship between the defendant's actions and the victim's death. This disregard implies weak legal protection for victims, legal uncertainty, and a dangerous precedent for judicial practice. Sociologically, this verdict injures the public's sense of justice, causes secondary victimization, reduces public trust, and demotivates the forensic medical profession. Systemic policies are needed, including Supreme Court guidelines, strengthening judges' capacity in forensic science, and institutionalized collaboration between institutions.